Ensino do ecoico na aquisição do mando em crianças com autismo - Giolo, Mayara Cristina Freitas Pereira (Universidade Federal de São Carlos, 2020)
Children diagnosed with the Autism Spectrum Disorder (ASD) present a delay in speech and language. Several researches have been developed to increase, decrease or put under control the frequency of specific stimulus of verbal behaviors for autistic people treated based on the Applied Behavior Analysis. Echoic vocal and mand behaviors are the initial repertoire to speak and that is the reason why they are such important teaching programs in autism treatment. The objectives consisted to install the repertoires of echoic and mand to analyze the effects of the echoic training for the mand acquisition, comparing to the effectiveness of the mand with echoic training in matters to analyze the effects of just mand training. Two children diagnosed with autism participated in this research. The reversal experimental design was used, children were evaluated to analyze the repertoire of the baseline with the VB MAPP – Verbal Behavior Milestones Assessment and Placement Program and Generalized Echoic Test instruments, subsequently each one was subjected to the teaching of a verbal operant. Right after the operant teaching the mand behavior acquisition was analyzed and the child that was initially trained by the echoic presented a significant increase in the mand repertoire compared to the child that was trained only with mand training.
Teaching echoic in the acquisition of mand in children with autism
Keywords: Autismo; Análise do comportamento aplicada; Ensino de ecoico; Mando; Autism; Applied behavior analysis; Echoic teaching; Mand; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO